Model of Remuneration: ‘Catching up’ Type (Russian Case) - GRETCHENKO, Anatoliy Ivanovich; DEMENKO, Olga Gennadevna; GRETCHENKO, Alexander Anatolievich (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).10, 2018)
Purpose : the aim of our research is the development of the theory and methodology of wages from the position of institutional and complementary approaches which encourage formation and implementation of the compensation model of payment at the corporate level, in the background of which the market price of labor lies, which is determined in the process of interaction of employment relations actors. Design/methodology/approach : this paper is based on the description and analysis of payment in Russia Findings : based on the empirical analysis of Russian and foreign literature, the author showed a trend of ‘catching up’ development wages model in Russian’s organizations. The author introduced scientifically based historical allocation of payment model development in Russia and suggested their classification. The conceptual framework of payment institution has been expanded. The conceptual approaches to forming the compensation model of payment at the corporate level have been reasoned. The mechanism of development and implementation of the compensation model of payment at the corporate level has been proposed. It has been proved that the contents of the ‘grading’ process using Western methods of job evaluation is identical to the content of the ‘tariff regulation’ and represents the reducing of labor at the corporate level. Author's definition of a social package has been justified. Originality/value : the paper discusses and develops conceptual frameworks, theoretical and methodological approaches to payment in Russia in the context of lessons derived from developed countries, as well as the guidelines to improve the mechanism of remuneration at the corporate level with regard to the economic conditions of modernization; the author considers that scientific findings will be of value for companies and their corporate governance.